Indomethacin Enhances Type 1 Cannabinoid Receptor Signaling - Laprairie, Robert B.; Mohamed, Kawthar A.; Zagzoog, Ayat; Kelly, Melanie E. M.; Stevenson, Lesley A.; Pertwee, Roger; Denovan-Wright, Eileen M.; Thakur, Ganesh A. (Frontiers in Molecular Neuroscience, 2019)
In addition to its known actions as a non-selective cyclooxygenase (COX) 1 and 2 inhibitor, we hypothesized that indomethacin can act as an allosteric modulator of the type 1 cannabinoid receptor (CB1R) because of its shared structural features with the known allosteric modulators of CB1R GAT211. Indomethacin enhanced the binding of [3H]CP55940 to hCB1R and enhanced AEA-dependent [35S]GTPγS binding to hCB1R in CHO cell membranes. Indomethacin (1 µM) also enhanced CP55940-dependent arrestin1 recruitment, cAMP inhibition, ERK1/2 and PLCβ3 phosphorylation in HEK293A cells expressing hCB1R, but not in cells expressing hCB2R. Finally, indomethacin enhanced the magnitude and duration of CP55940-induced hypolocomotion, immobility, hypothermia, and anti-nociception in C57BL/6J mice. Together, these data support the hypothesis that indomethacin acted as a positive allosteric modulator of hCB1R. The identification of structural and functional features shared amongst allosteric modulators of CB1R may lead to the development of novel compounds designed for greater CB1R or COX selectivity and compounds designed to modulate both the prostaglandin and endocannabinoid systems.